The influence of mobile money services on customers in the Bolgatanga municipality, Ghana - Mahama, Fuseini; Bunyaminu, Alhassan; Ayimpoya, Redruth Nyaaba; Combert, James (Edelweiss Applied Science and Technology, 2024)
Mobile telecommunications can help low-income countries improve their fixed-line and internet infrastructures. Mobile phones boost information availability, reduce search costs, facilitate supply coordination, and benefit low-income people. Mobile banking, often known as m-money, uses mobile networks to allow account balance queries and money transfers without the use of physical infrastructure. Ghanaians strongly prefer mobile money transfer services because of their low cost and accessibility across all economic strata. These simple and dependable services are suitable for clients who have little financial means, as most Ghanaians do. There has been very little empirical research into the benefits and challenges of mobile money services. Because of a paucity of data at the individual level, research into the penetration of financial services in low-income countries such as Ghana is limited. This study looks at both the advantages and disadvantages of using mobile money services. The study analyzed data from a mobile money survey using Partial Squares Structural Equation Modelling (PLS-SEM). This evidence supports the hypothesis that benefits will increase customer sentiment, while restrictions will decrease patronage. The researchers will conduct additional research into the theoretical and practical implications of mobile money systems' benefits and drawbacks for consumers. It supports the hypothesis that advantages improve consumers' perceptions, while impediments reduce patronage. Additional research will consider both the theoretical and practical implications of mobile money systems' benefits and challenges for users.